A model with options and order cancellation for in-season replenishment - Kızılkan, Nihan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
We investigate a model with options and order cancellation in a buyer-supplier system for in-season replenishment. We analyse the model in two periods with correlated demand. We derive the appropriate prices that the supplier must choose for channel coordination, however individual rationality constraint of the supplier is violated. Finally, using a computational study, we quantify the value of options and order cancellation combination. We demonstrate that options and order cancellation combination provides flexibility to the buyer to respond to market changes thus increasing the total expected profit even more than the options-only model.
Keywords: Business logistics.